Assessment methods in undergraduate medical schools - Asani, Mustafa (Nigerian Journal of Basic and Clinical Sciences, 2026)
Assessment in medical education is very vital because of its far reaching implications not only for the students and their teachers but for the communities and world at large. This article attempts to review the assessment methods used in undergraduate medical schools, highlight their limitations while proffering solutions as recommended by experts in medical education. Assessment methods that are used in the undergraduate medical education can be broadly subdivided into two; assessment of knowledge and its application (Multiple choice questions, essay and viva voce) and assessment of clinical competence (long case, short case and objective structured clinical examination [OSCE]). There are five major criteria for determining the usefulness of a particular method of assessment: Reliability, Validity, Educational impact, Cost effectiveness and Acceptability. The major drawback of the long and short case examinations is the poor reliability or reproducibility due to case specificity, inter examiner and clinical case scenario variability. In 1975, Hardenet al., introduced the OSCE to avoid the disadvantages of long case but acceptability may be an issue because of inadequate exposure to its principles and resistance to change by some teachers. Another objective version of the long case is the objective structured long examination records. Objective structured practical examination is also preferred to the traditional practical examinations in laboratory based courses. All assessment methods have their strengths and limitations. It is important that teachers in medical schools are aware of the limitations of the traditional assessment tools and embrace newer and more reliable methods of assessment.
Keywords: Assessment; medical schools; undergraduate